Revisiting Family Leisure Research and Critical Reflections on the Future of Family-Centered Scholarship. (3rd September 2017) - Trussell, Dawn E.; Jeanes, Ruth; Such, Elizabeth
ABSTRACT: In this special issue of Leisure Sciences, we examine the progress made and challenges ahead in research on leisure and families—20 years revisited. We consider what advancements have been made in family leisure research and potential new directions that family-centered scholars can look towards. We also consider the dominance of particular theoretical perspectives and methodological designs, and the limitations and consequences of such perspectives, to understand the complexities, diversity, and richness of the lived family experience. Emphasis is placed on the need for scholarship that explores diverse constructions of family and to provide a call to action for family-centered scholars to engage with broader global social issues.